Persepsi Petani Terhadap Konsep Ketahanan Pangan Melalui Ekonomi Kebersamaan di Kabupaten Situbondo: (Farmer’s Perceptions of the Concept of Food Security through the Economy of Togetherness in Situbondo Regency) - Duwi Yunitasari; Fivien Muslihatinningsih; Herman Cahyo Diartho; Endah Kurnia Lestari; Agus Lutfi (e-Journal Ekonomi Bisnis dan Akuntansi, 2021)
The purpose of this study was to identify farmers' perceptions of the concept of food security through an economic model of togetherness in Situbondo Regency. The data source of this research was obtained by observation, FGD and questionnaires with the data method using logistic regression analysis with farmer analysis units (food crops, breeders and fish cultivators) in Situbondo district. Based on the binary logistic regression equation shows that the perceptions of farmers, breeders and fish cultivators a positive and significant impact on the concept of food security, the economic model of togetherness is income and infrastructure. Therefore, for farmers, ranchers and cultivators, along with the increase in income earned and accompanied by easier opportunities to gain access to market infrastructure from the local government, the concept of food security with an economic model of togetherness is acceptable.